The storyteller's death : a novel - Cardinal, Ann Dávila (Sourcebooks Landmark, 2022)
"There was always an old woman dying in the back room of her grandmother's house when Isla was a child... Isla Larsen Sanchez's life begins to unravel when her father passes away. Instead of being comforted at home in New Jersey, her mother starts leaving her in Puerto Rico with her great-aunt each summer, like a piece of forgotten luggage. It is only when Isla turns eighteen, and her grandmother, a great storyteller, dies, that Isla discovers she has a gift. The tales of dead family storytellers are brought back to life, replaying themselves over and over in front of her. When Isla has a vision of an old murder mystery, she realizes that if she can't solve it to make the loop end, these seemingly harmless stories could cost Isla her life"--